Emerging Marine Biotoxins - Gerssen, Arjen (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The emergence of marine and freshwater toxins in geographical areas where they have never been reported before is a concern due to the considerable impact on (sea)food contamination, and consequently, on public health. Several groups of marine biotoxins, in particular tetrodotoxins, ciguatoxins, and palytoxins, are included among the relevant marine biotoxins that have recently emerged in several coastal areas. A similar situation has been observed in freshwater, where cyanobacterial toxins, such as microcystins, could end up in unexpected areas such as the estuaries where shellfish are cultivated. Climate change and the increased availability of nutrients have been considered as the key factors in the expansion of all of these toxins into new areas; however, this could also be due to more intense biological invasions, more sensitive analytical methods, or perhaps even an increased scientific interest in these natural contaminations. The incidences of human intoxications due to the consumption of seafood contaminated with these toxins have made their study an important task to accomplish in order to protect human health. This Special Issue has a focus on a wide variety of emerging biotoxin classes and techniques to identify and quantify them.